IMPACT OF AN EXTRAVAGANT LIFESTYLE ON CYBERCRIME AMONG UNIVERSITY STUDENTS IN IBADAN: THE MEDIATING EFFECT OF EMOTIONAL INTELLIGENCE - Adegbite, Obasanjo Sanya; Ojo, Solomon; Olonade, Zacheaus Olufunminiyi; Adu, Richard Akinjide (African Journal of Social and Behavioural Sciences, 2024)
Cybercrime is an illegal means of acquiring wealth through the use of computers and the internet. It involves a range of actions with digital devices and internet networking. This attitudinal behaviour is very common among undergraduate students and predisposes both perpetrators and victims to different psychological imbalances and deaths. Earlier studies have neglected the link between an extravagant lifestyle and cybercrime, and the potential of emotional intelligence to ameliorate connectivity. This study attempted to fill this vacuum in knowledge adding to the literature on cybercrime. This study was based on the psychoanalytic theory of “id” personality, which operates on the pleasure-seeking principle. A cross-sectional survey design was utilized and a multistage sampling technique was used to select three hundred and five participants ages between 16 to 25 years. Cybercrime was measured through a 20-item criminality scale and a 34-item extravagant Lifestyle Assessment Scale (ELAS). Response format ranges from 1 equal strongly disagree and 5 equal strongly agree. A significant direct impact of an extravagant lifestyle on cybercrime (β=0.42; t= 9.63; p<.001) was observed. Additionally, an extravagant lifestyle had a significant direct impact on emotional intelligence (β=0.42; t= 8.05; p<.001). Emotional intelligence has a direct impact on cybercrime (β=0.48; t= 8.05; p<.001) and partially mediates consanguinity between extravagant lifestyle and cybercrime (β=-.18; t = .032; p<.001). This study recommends extravagant lifestyle sensitization by Parents, NGOs and religious leaders. Emotional intelligence training by institutions is recommended to ameliorate cybercrime. Intensive internet surveillance by the government is recommended to curtail cybercrime and a Cognitive rehabilitation programme is recommended for the arrested victims of cybercrime.